The trade effects of endogenous preferential trade agreements - Peter Egger; Mario Larch; Kevin E. Staub; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2010)
Recent work by Anderson and van Wincoop (2003) establishes an empirical modeling strategy which takes full account of the structural, non-(log-)linear impact of trade barriers on trade in new trade theory models. Structural new trade theory models have never been used to evaluate and quantify the role of endogenous preferential trade agreement (PTA) membership for trade in a way which is consistent wth general equilibrium. Apart from this gap, the present paper aims at delivering an empirical model which takes into account both that preferential trade agreement membership is endogenous and that the world matrix of bilateral trade flows contains numerous zero entries. These features are treated in an encompassing way by means of (possibly two-part) Poisson pseudo-maximum likelihood estimation with endogenous binary indicator variables in the empirical model.
Keywords: F14; F15; 330; Gravity model; Endogenous preferential trade agreement membership; Poisson pseudo-maximum likelihood estimation with endogenous binary indicator variables; Neue Außenhandelstheorie; Handelspräferenzen; Handelseffekt; Maximum-Likelihood-Methode; Welt